Answers

The Brainliest Answer!
2015-05-10T19:43:04+05:30
Given Sn = 4n - n²
taking n=1, we get,
S1 = 4×1-1² = 4-1 = 3
if n=2, then S2 = 4×2 -2² = 8-4 = 4
if n=3, then S3 = 4×3-3² = 12-9 = 3
if n=4, then S4 = 4×4-4² = 16-16 = 0 ....
Hence S1 = a or a1 = 3
then a2 = S2-S1 = 4-3 =1
       
a3 = S4-S3 = 0-3 = -3
therefore a3 = 1

So, d= a2-a1 = 1-3 = -2

from above, we get,
a=3, d= -2
then,
a10 = a+9d
      = 3+9(-2)
      = 3-18
      = -15
therefore, a10 = -15

an = a+(n-1)d
     = 3+(n-1)(-2)
     = 3-2n+2
     = 5-2n
therefore, an = 5-2n
     

2 5 2
plzz click on thanks n mark it as best... hope it helps
thank u very very much
bro dont have to say thanks to their siso :P
hey sis i said no
okok :)